Incivility, bullying, and poor health and well-being among students: a Swedish national study in higher education institutions - Mensah, Aziz; Toivanen, Susanna; Björklund, Christina (Frontiers in Public Health, 2024)
Objective: Exposure to incivility and bullying among students in higher education institutions may have detrimental health and well-being outcomes. Nevertheless, the mechanism and interconnected pathways through which incivility and bullying are linked with poor health and well-being remain largely unexplored. The aim of this study is to investigate the relationships between incivility, bullying, and poor health and well-being among students in higher education institutions in Sweden, and whether gender influences these relationships.Furthermore, we examine whether bullying plays a mediating role in the relationship between incivility and poor health and well-being.We analyzed a cross-sectional dataset of students drawn from 38 universities that are members of the association of Swedish higher education institutions. The data were collected from May to July 2021, covering 11,162 women and 6,496 men. Confirmatory factor analysis and structural equation modeling (SEM) were utilized to estimate the relationships between incivility, bullying, and poor health and well-being. Additionally, multigroup analysis was applied to estimate the interactive effect of gender in these relationships.Results: Reports of both incivility and bullying were more prevalent among women than men.The results showed that incivility had direct relationships with both bullying (𝛽𝛽 = 0.578, 𝑃𝑃 < 0.01) and poor health and well-being (𝛽𝛽 = 0.301, 𝑃𝑃 < 0.01). However, the relationship between bullying and poor health and well-being was not significant. There were statistically significant gender differences in the relationships between incivility, bullying, and poor health and well-being (△ 𝜒𝜒 2 (23) = 179.18, p < 0.01). Nevertheless, bullying did not significantly mediate the relationship between incivility and poor health and well-being.The current study demonstrates that governments, university authorities, and policymakers must consider gender differences in incivility and bullying when developing policies and interventions intended to reduce these kinds of behaviors in organizations.